Effect of Different Coating Techniques with Aluminum on the Corrosion Behavior of Stainless Steel 316L in Seawater - Ataiwi, Ali H; Hamood, Abdul Khaliq F; Majed, Rana A (Al-Nahrain Journal of Science, 2012)
This study involves effect of aluminum coating by using different techniques (Aluminizing, Flame spraying, and Hot dipping) on corrosion behavior of stainless steel 316L in seawater. Cathodic and anodic regions are studied by using potentiostat to measure the corrosion parameters through Tafel method which include open circuit potential (Eocp), corrosion potential (Ecorr), and corrosion current density (icorr) in addition to calculation of coating corrosion rates (R). The results indicate that the corrosion rate for coated specimens by aluminizing and flame spraying techniques were less than the values before coating but coating with hot dipping technique gives higher rate than the non coated samples, where the results take the following sequence: Corrosion coating sample < coating sample < coating sample Rate (μm/y) by using pack using flame spray using hot dipping cementation aluminizing The potentials with time were interpreted in order to study the evolution of the film chemistry as it came to equilibrium with solution where the results observed that the aluminum coating by aluminizing reaches to the steady – state faster than other samples. Also the galvanic current density with time were discussed where the results indicates, in general, the transients for specimens show an initial sharp decrease in galvanic current exhibited by all coated specimens followed by a more steady, but erratic decrease in the galvanic current.